Enhancing electromagnetic wave absorption with core‐shell structured SiO2@MXene@MoS2 nanospheres - Xuewen Jiang; Qian Wang; Limeng Song; Hongxia Lu; Hongliang Xu; Gang Shao; Hailong Wang; Rui Zhang; Changan Wang; Bingbing Fan (Carbon Energy, 2024)
Abstract Material composition and structural design are important factors influencing the electromagnetic wave (EMW) absorption performance of materials. To alleviate the impedance mismatch attributed to the high dielectric constant of Ti3C2Tx MXene, we have successfully synthesized core‐shell structured SiO2@MXene@MoS2 nanospheres. This architecture, comprising SiO2 as the core, MXene as the intermediate layer, and MoS2 as the outer shell, is achieved through an electrostatic self‐assembly method combined with a hydrothermal process. This complex core‐shell structure not only provides a variety of loss mechanisms that effectively dissipate electromagnetic energy but also prevents self‐aggregation of MXene and MoS2 nanosheets. Notably, the synergistic combination of SiO2 and MoS2 with highly conductive MXene enables the suitable dielectric constant of the composites, ensuring optimal impedance matching. Therefore, the core‐shell structured SiO2@MXene@MoS2 nanospheres exhibit excellent EMW absorption performance, featuring a remarkable minimum reflection loss (RLmin) of −52.11 dB (2.4 mm). It is noteworthy that these nanospheres achieve an ultra‐wide effective absorption bandwidth (EAB) of 6.72 GHz. This work provides a novel approach for designing and synthesizing high‐performance EMW absorbers characterized by “wide bandwidth and strong reflection loss.”